Profil Keterampilan Berpikir Kritis Siswa Kelas V Sekolah Dasar pada Pembelajaran IPAS - Tambunan, Rifka Paulina; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2025)
This study aims to provide a comprehensive profile of the critical thinking skills of fifth-grade students at SDN Totosari Surakarta. Ultimately, this profile can contribute to improving IPAS teaching practices and student learning experiences. The research employs a qualitative descriptive method, utilizing critical thinking skills tests and observations for data collection. The subject are 24 fifth-grade students from SDN Totosari in Surakarta. The observation technique was carried out during learning activities. The test consisted of essay questions related to the learning topic. The result indicate that there are 6 students in the high and very high categories, and 8 students in the moderate category. Therefore, it can be concluded that most students possess critical thinking skills.